The Role of Duck as The National Producer of Egg and Meat - Pius P Ketaren (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
Ducks produce egg, meat and feather. Egg is the main product of ducks for Indonesian communities. Duck farming produced eggs approximately 180,000 ton or equal to 16% of national egg production in 2005. Ducks also contributed 38,700 tons of meat or 3% of national poultry meat production or equal to 2% of national meat production. Besides egg and meat, duck farming also produced 269.4 tons of feather valued at US $ 294,800. All of those duck commodities were produced by 35 million of hearded ducks. Hearded ducks productivity were approximately 100 – 150 eggs/hen/year which were considered to be much lower than confined ducks productivity which were recorded at average of 253 eggs/hen/year. There are known several local Indonesian ducks which showing highly variable egg productivities. Various technologies are potential to be implemented by duck farmers to improve their duck-egg production. The improvement can be achieved by implementing breeding and nutrition technologies such as replacing the old hens with selected local duck breeds, feeding appropriate diets and implementing good management practices in their farms.   Key words: Duck, role, egg, meat, technology